Fishermen Household Organization and Division of Duties in Fisherman Households in South Maitara Village Tidore CityIslands - Nuraini A. Damsiki (International Journal of Education, Information Technology, and Others, 2020)
The purpose of this study is to uncover and study the form of fishing household community organizations in South Maitara Village, and to identify the types of roles in fishing households and the distribution of these roles to each family member of the fishing household community in South Maitara Village. The research method used is a case study that is an approach that aims to maintain the needs of the object to be studied. Case studies must be characterized as explorative research (Vredenbregt, 1980). The research sample is a fishing household community in South Maitara village, fishing households in South Maitara village are 32 RTN. The results showed that the fishermen household organization is a combination of cooperation between family members in the fishing household in order to achieve the desired goals. The fishing household community in the village of South Maitara shows that there is harmony between family members in carrying out each of their roles. The role of family members of the fishing household community in South Maitara is still very dependent on the fulfillment of the household economy, the results of the study indicate that in general the role of household members, especially children, is more concentrated in domestic activities, where the division of tasks is carried out based on the ability of their children and gender